2017
DOI: 10.1002/2017jc013265
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemistry of Dimethylsulfide, Dimethylsulfoniopropionate, and Acrylic Acid in the Changjiang Estuary and the East China Sea

Abstract: The distributions of dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), and acrylic acid (AA) were investigated in the Changjiang Estuary during winter (dry season) and summer (wet season) 2014 and in the East China Sea (ECS) during summer 2015. The rates of dissolved DMSP (DMSPd) degradation with DMS and AA production, DMS degradation, and AA degradation in the ECS were also studied. Significant seasonal variations in DMS(P) and AA concentrations were observed in the Changjiang Estuary with higher valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 93 publications
2
6
0
Order By: Relevance
“…DMSPt had a positive correlation with temperature and a negative correlation with salinity (Table 2). Many other investigations also reported analogous correlations (Shenoy and Patil, 2003;Deschaseaux et al, 2014;Wu et al, 2017). In winter, transect B57-63 was inaccessible to sampling due to frozen conditions; thus, we only report the results of transect B12-16 in the NYS and transect H19-26 in the SYS.…”
Section: Vertical Distributions Of Aad Dms and Dmsp In The Bs And Yssupporting
confidence: 52%
See 2 more Smart Citations
“…DMSPt had a positive correlation with temperature and a negative correlation with salinity (Table 2). Many other investigations also reported analogous correlations (Shenoy and Patil, 2003;Deschaseaux et al, 2014;Wu et al, 2017). In winter, transect B57-63 was inaccessible to sampling due to frozen conditions; thus, we only report the results of transect B12-16 in the NYS and transect H19-26 in the SYS.…”
Section: Vertical Distributions Of Aad Dms and Dmsp In The Bs And Yssupporting
confidence: 52%
“…The incubation experiments for DMSPd and AAd degradation were conducted on deck using seawater collected at stations H19, H26, B12, B17, B53, and B63 in summer and at H19, H26, B12, and B16 in winter, following the method of Wu et al (2017). We determined the degradation rates of DMSPd and the production rates of DMS and AAd by incubating unfiltered seawater samples in two 250 mL gastight glass syringes (wrapped in aluminum foil) in the dark at in situ temperatures.…”
Section: Incubation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of correlation may be due, in part, to variation in DMSPd loss pathways. The DMS yield of DMSP metabolism can vary significantly depending on metabolic needs of bacteria present and the relative abundance of phytoplankton with DMSP lyase activity (Yoch, 2002). Although DMS yield was not measured in this study, previous reports have shown that in the NESAP a low carbon to organic sulfur ratio in the HNLC regime results in increased DMS yield from DMSP metabolism, whereas onshore DMS yield is relatively lower (Merzouk et al, 2006;Royer et al, 2010).…”
Section: The Effect Of Dms and Dmsp Consumption Rate On Dms Distributionmentioning
confidence: 72%
“…DMSPt showed a positive correlation with temperature and a negative correlation with salinity (Table 2). Many other investigations also reported the analogous correlations (Deschaseaux et al, 2014;Shenoy and Patil, 2003;Wu et al, 2017). It has been reported that 225 lower salinity could enhance algal DMSP lyase activity (Stefels, 2000), which might have led to the negative correlation between DMSP and salinity.…”
mentioning
confidence: 58%